Pengaruh Penambahan Tepung Rumput Laut terhadap Daya Terima Nasi IR 64 - Fauzi, Fa'izah; Alsuhendra, Alsuhendra; Efrina, Efrina (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2023)
IR 64 rice in Indonesia are among the highest sold, with a percentage of 26.09% while IR 42 rice was 10%, Muncul rice was 8.24% and Setra Ramos rice at 5.94%. However, white rice has a low fibre content. This research was conducted to determine the effect of adding seaweed flour (Eucheuma spinosum) on consumer acceptance of IR 64-cooked rice. The aspects studied were rice's taste, colour, aroma, and texture. This research started with making seaweed flour, which added 0.5% CaO as a bleaching agent during the soaking process. Then the seaweed flour was added to the rice before cooking at different contents of 5, 6, and 7%. Furthermore, the rice is cooked using Liwet technique. This rice was then tested organoleptically with four expert panelists (Culinary Education lecturers) and 30 semi-trained panelists (students of the Pendidikan Tata Boga Program, Universitas Negeri Jakarta). Based on the results of the Friedman test, with a confidence level of 95%, it shows that there is no influence on the aspects of aroma, texture, and colour, but there is an influence on the aspects of taste. Tukey's test results with α= 0.05 showed a tendency for liking the addition of 6% flour. According to 4 expert panelists, adding 6% has the characteristic taste of rice that is almost strong; the colour is close to the original white rice. The aroma of seaweed is barely prominent and has an almost fluffier texture.